Role of Artificial Neural Network in an Intelligent Educational System - Bhari, Purushottam Lal; CD, Kumawat (International Journal of Computer Sciences and Engineering, 2019)
Artificial Neural Network (ANN) is an important part of the artificial brain. This study presents the promise ofartificial neural network in development of artificial brain and controls intelligent educational systems. Some important factors that may influence the performance of artificial neural network are outlined in this research paper. Moreover, applications of a variety of neural network architectures in intelligent educational systems are surveyed. Further an attempt has been made to explore the relations between the fields of natural science and neural networks in a unified presentation.